Bivalent oral cholera vaccine in participants aged 1 year and older in the Dominican Republic: A phase III, single-arm, safety and immunogenicity trial - Lina Cordero De Los Santos; Jesús Feris-Iglesias; Naveena Aloysia D'Cor; Venkata Jayanth Midde; Badri Narayan Patnaik; Yaël Thollot; Anvar Rasuli; Eric Desauziers (Taylor & Francis Group, 2018)
The Dominican Republic, historically non-endemic for cholera, is experiencing an ongoing cholera epidemic. We assessed the safety and immunogenicity of two doses of the killed bivalent (O1 and O139) whole-cell oral cholera vaccine (OCV) on day (D)0 and D14 in healthy participants aged ≥1 year. Immediate unsolicited systemic adverse events (AEs) were monitored up to 30 minutes and solicited systemic reactions, up to 7 days after each vaccination. Unsolicited AEs were recorded up to D14 (post-dose 1) and 30 days post-dose 2. A vibriocidal antibody assay with microtiter technique was used to measure serum antibodies to V. cholerae strains (O1 El Tor Inaba, O1 El Tor Ogawa, O139) on D0, D14 and D28. Geometric mean titers (GMTs) and seroconversion (≥4-fold increase from D0) rates were calculated. We recruited 336 participants; 112 in three age groups (1-4, 5-14 and ≥15 years). No safety concerns were observed. GMTs increased from baseline for all serotypes, with marked increases for O1 Inaba and Ogawa post-dose 1. Post-dose 2 GMTs tended to be equal or slightly lower, with ranges: O1 Inaba, 283 (95% confidence interval 191-419) to 612 (426-880); O1 Ogawa, 346 (223-536) to 754 (553-1028); and O139, 20.3 (13.5-30.6) to 43.8 (30.1-63.7). Seroconversion rates post-dose 2 for O1 Inaba and Ogawa were high (≥87%) for all age groups. OCV demonstrated an acceptable safety profile and robust immunogenicity in these participants, in-line with previous observations in epidemic and endemic settings.This study is registered on www.clinicaltrials.gov (NCT02434822).